EFEKTIVITAS PENERAPAN METODE PEMBELAJARAN ROLE PLAYING PADA SISWA KELAS XI IPA 2 SMA YPPK TARUNA DHARMA KOTARAJA DALAM MENINGKATAKAN KETERAMPILAN BERBICARA - Mandowen, Kartika Yuliana (JURNAL TRITON PENDIDIKAN, 2016)
This paper aims to reveal the application of learning methods Role Playing is a method that seeks to provide mastery of learning materials through the development of imagination and appreciation. Implementation of Role Playing learning method is aimed to train the students of grade XI IPA 2 SMA YPPK Taruna Dharma so that the students are skilled to speak and dare to express by paying attention to mimic, gestures and intonation in the context of drama play. Speaking aims to express ideas and opinions, criticisms, feelings in various forms to the speaking partner according to the purpose and context of the conversation. In addition, through the activities of speaking and communicating students can gain new experiences and can appreciate the literature in various types and forms through the activities of oral literary results This paper explores the use of learning methods Role Playing which aims to provide mastery of learning materials through the development of imagination and appreciation.